Implementasi Sistem ERP Menggunakan Odoo Modul Point Of Sales pada UMKM Sambel Korek DNO - Chindy Cantika Setiani; Lufty Abdillah (UNIVERSITAS KALBIS, 2023)
Information technology is an important factor in achieving success in the information sector, one of the information technologies used in this research is implementing an ERP (Enterprise Resource Planning) system for SMEs. MSME Sambel Korek DNO is one of the medium-sized businesses engaged in Culinary and is located at Jalan Sumur Batu Raya No. 416 Kemayoran District, Central Jakarta. MSME Sambel Korek DNO provides food and drinks that can be enjoyed with family or friends. The problem with Sambel Korek DNO SMEs is that the recording of orders and sales reports is still done manually, namely recording with paper or written notes so that it is less effective during the business process. This study aims to create a system that can facilitate Sambel Korek DNO SMEs in recording purchase orders and recapitulating sales data reports in a short time using the Accelerated SAP (ASAP) method. The results of this study apply the Odoo ERP system with the Point Of Sales module and support other Odoo modules.